Friedrich Nietzsche's Impact on Modern German Literature : Five Essays - Reichert, Herbert W. (Chapel Hill The University of North Carolina Press, 1975)
These previously published essays discuss Nietzsche's influence on Arthur Schnitzler, Carl Sternheim, Georg Kaiser, Robert Musil, and Hermann Hesse. As a Festschrift, it also contains a tribute to Herbert W. Reichert and a bibliography of his writings.
National Endowment for the Humanities
Andrew W. Mellon Foundation
English
Keywords: Literature: history & criticism; German Studies; Literature